2009
DOI: 10.1152/jn.00650.2009
|View full text |Cite
|
Sign up to set email alerts
|

Slow Excitation of Cultured Rat Retinal Ganglion Cells by Activating Group I Metabotropic Glutamate Receptors

Abstract: Yu J, Daniels BA, Baldridge WH. Slow excitation of cultured rat retinal ganglion cells by activating group I metabotropic glutamate receptors. J Neurophysiol 102: 3728 -3739, 2009. First published October 21, 2009 doi:10.1152/jn.00650.2009. As in many CNS neurons, retinal ganglion cells (RGCs) receive fast synaptic activation through postsynaptic ionotropic receptors. However, the potential role of postsynaptic group I metabotropic glutamate receptors (mGluRs) in these neurons is unknown. In this study we fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…This is consistent with the observation in cultured rat RGCs that DHPG increased spontaneous spiking and depolarized the membrane potential of RGCs, which were mediated by mGluR1 rather than mGluR5 (Yu et al 2009). Regarding the expression of mGluR I subunits, although in situ hybridization and immunohistochemical studies have shown that the expression of mGluR1, 2, 4, and 7, but not mGluR3, 5 or 6, was detected in the GCL (Hartveit et al 1995), all types of mGluR mRNAs were found in RGCs by single-cell RT-PCR (Tehrani et al 2000).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the observation in cultured rat RGCs that DHPG increased spontaneous spiking and depolarized the membrane potential of RGCs, which were mediated by mGluR1 rather than mGluR5 (Yu et al 2009). Regarding the expression of mGluR I subunits, although in situ hybridization and immunohistochemical studies have shown that the expression of mGluR1, 2, 4, and 7, but not mGluR3, 5 or 6, was detected in the GCL (Hartveit et al 1995), all types of mGluR mRNAs were found in RGCs by single-cell RT-PCR (Tehrani et al 2000).…”
Section: Discussionsupporting
confidence: 92%
“…currents in cultured mouse RGCs (Rothe et al 1994) and in RGCs of salamanders (Akopian and Witkovsky 1996;Shen and Slaughter 1998), but had no effects on spontaneous or evoked excitatory postsynaptic currents (EPSCs) in RGCs of salamanders (Awatramani and Slaughter 2001;Higgs et al 2002). In a recent report, Yu et al (2009) showed that activation of mGluR I modulated the intrinsic excitability of rat RGCs in culture by reducing background K ? conductance.…”
Section: Introductionmentioning
confidence: 99%
“…This observation may indicate that K2P channels perform important roles in vision. Glutamate is the key neurotransmitter by which bipolar cells transmit rod and cone derived signals to RGCs757677, and a previous study has described the presence of a glutamate sensitive background leak type K + current in cultured mouse RGCs with properties of a TASK like current, most likely TASK-1 or TASK-378. Inhibition of this TASK-type current by the group I mGluR agonist ( S )-3,5-dihydroxyphenylglycine (DHPG) results in the depolarisation of retinal ganglion cells and increased levels of action potential firing, suggesting a significant role for TASK type channels in the regulation of RGC excitability by glutamate.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility, suggested by Vigh et al [15], is that mGlu1 receptor activation increases the release probability of GABA release directly through an increase in intracellular Ca 2+ levels. More recently, Yu et al [26] found that in a rat RGC-astroglia coculture system, activation of mGlu1 receptors depolarizes RGCs by blocking a background K + conductance in these cells. Although undoubtedly there are other yet to be discovered functional roles for mGlu1 receptors in the retina, the effects of the mGlu1 receptor antagonist JNJ16259685 observed in the present study can largely be explained by the modulation of GABA release from amacrine cells onto bipolar cells.…”
Section: Discussionmentioning
confidence: 99%